Tensile mechanical response of polyethylene – clay nanocomposites. (eXPRESS Polymer Letters)
In this work we report on the microstructural and the mechanical characteristics of high density polyethylene (HDPE)-clay nanocomposites, with particular attention to the creep behaviour. The samples were prepared through melt compounding, using two high-density polyethylenes with different melt flow rate (MFR), two different organo-modified clays, and changing the relative amount of a polyethylene grafted with maleic anhydride (PEgMA) compatibilizer. The intercalation process is more effective as the matrix melt viscosity decreases (higher MFR), while the clay interlamellar spacing increases as the compatibilizer amount increases. The relative stiffness of the nanocomposites increases with the addition of clay, with a limited enhancement of the relative yield stress. The better intercalation obtained by the addition of the compatibilizer is not accompanied by a concurrent improvement of the tensile mechanical properties. The creep resistance is enhanced by the introduction of clay, with an appreciable dependence on both the polyethylene and the clay type.